THE EFFECT OF THERAPEUTIC GROUP THERAPY (TGT) FOR MIDDLE AGED ADULTS ON THE RESILIENCE OF COASTAL RESIDENTS AFTER THE COVID-19 PANDEMIC - Nurul Huda; Bagus Dwi Cahyono; Evy Aristawati; Dody Wijaya (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Almost everyone has been directly or indirectly affected by the COVID-19 virus pandemic. Many people are not ready to adapt to sudden lifestyle changes. This causes some people to experience fear and anxiety. Objectives: The study aimed to analyze group therapy effect on coastal resident’s resilience after the Covid-19 pandemic. Methods: This study uses Quasy Experimental Pre-Posttest design, with 2 groups. The location of this research is in the northern coastal area of Pasuruan City and Regency. The sampling technique of this study used purposive sampling, a total of 20 respondents were divided into two group, namely the control grouop and the treatment group. To mesuare the level of resiliensi all the responden were given The pretest and post test carried out using instruments to determine community resilience after the Covid-19 pandemic using the Resilience,however only the treatment group was given the TKT interventio. Processing and testing of data using SPSS software, with the Wilcoxon statistical test with α = 0.05. Results: The results of the study with the Wilcoxon statistical test in the treatment group obtained a value of p = 0.001 (p <0.05) and in the control group obtained a value of p = 0.083 (p > 0.05)this means there is a significant difference between the control group and the treatment group. Conclusion: This study concludes that there is a significant difference in the resilience of the community during the pretest and posttest in the treatment group receiving therapeutic group therapy, and there is no significant difference in the strength of the coastal community during the pretest and posttest in the control group. For this reason researchers suggest regularly holding this TKT for residents to increase the resiliensi of coastal residents.